INVESTIGATING STUDENTS' SPEAKING ANXIETY IN CLASSROOM INTERACTION THROUGH ZOOM MEETING - Fatimah Awaliyah; Leni Irianti (Journal of English Education Program (JEEP), 2022)
Anxiety is a strong influence that interferes with the learning process to run well. Zoom cloud meeting is a collaborative, cloud-based videoconferencing service offering features including meetings, group messaging services, and secure recording of sessions. This research implemented a qualitative approach. A case study was applied as a research design. Research data were online classroom observation (non-participants observation) and interviews (semi-structured). The data analysis of this research was transcribing data,  coding, and concluding. The participant of this research was chosen purposively and it is an English teacher and third-grade students in Vocational high. The result from classroom observation determines 5 anxious students’ and it showed that the teacher give an impact on anxious students especially when the teacher adds media such as PowerPoint during classroom interaction through Zoom cloud meetings. Base on the result of the interview concluded that Zoom cloud meetings as a platform give students positive impacts to reduce their speaking anxiety in classroom interaction. This study concludes that Zoom cloud meeting makes the students’ felt easier and be confident to reduce their anxiety in classroom interaction. For further researchers, it is hoped that they will be able to explore more about the effectiveness of using Zoom cloud meeting to reduce students’ speaking anxiety in classroom interaction.